Comparison of maximum lactate between Course Navette Test and Hoff Test in soccer players at 2600 meters above sea level - León, H. H.; Ramirez, J. F.; Sánchez, A.; Salazar, J. D.; Orjuela, L.; Anzola, S. V. (Journal of Human Sport & Exercise, 2015)
Introduction: Nowadays football (soccer) requires a high aerobic capacity and for its assessment the Test of Course Navette (TCN) has been widely used. However, other tests closer to the current conditions like the Test of Hoff (TH) have also been applied. The study assessed the maximum production of lactate using both tests in similar conditions. Materials and Methods: 17 male soccer players were evaluated twice. One time using the TCN and the other time using the TH. At both times lactate was assessed at rest and at the end of maximum heart rate and lactate. The differences were statistically evaluated by Wilcoxon T and its correlation via a linear regression. Results: The initial lactate values were: TCN 4.9 ± 2.1 mmol/L and TH 4.2 ± 2.4 mmol/L, (p=0.162) Final lactate values: 11.6 ± TCN 3.3 mmol / L and TH 12.4 ± 3.8 mmol/L, (p=0.325), maximum heart rate 193.8 ± 9.3 beats TCN and TH: 188.1 ± 7.6 beats (p <0.05), the maximum speed reached at the TCN compared to the distance achieved by the TH, has a R2=0.55. Conclusion: TH is a test given under conditions closer to those of the game, and it has a strong relation with the TCN in the assessment of the aerobic capacity, without significant differences in the results of maximal lactate.